Dakwah bil Hal Pesilat Pagar Nusa di Temanggung - Sungkawaningrum, Fatmawati; Baehaqi, Muh. (Dakwah, 2025)
Pagar Nusa silat practitioner in Temanggung is a pencak silat school under the auspices of Nahdlatul Ulama. The frequent brawls between martial arts schools have motivated Pagar Nusa martial artists in Temanggung to engage in dakwah bil hal (preaching through actions) to prevent such conflicts from escalating. This research is a field study using a qualitative descriptive approach. The findings reveal that Pagar Nusa Temanggung applies nine stances that serve as the foundation of their movements while also reflecting profound philosophical and moral values. These stances not only regulate physical movements but also symbolize deep spiritual and ethical meanings. The nine stances are: pagar bangsa (national defense stance), tempel stance (close attachment stance), silang dada (cross-chest stance), pagar nusa (Pagar Nusa stance), silang bawah (low cross stance), kepal pinggang (fist-on-waist stance), sangkol (hook stance), lurus bawah (straight-down stance), and kuda-kuda kaki satu (one-legged horse stance). The implementation of dakwah bil hal values by Pagar Nusa silat practitioner in Temanggung includes: promoting unity in religious diversity, embodying humility and wisdom, upholding the principle of Islam rahmatan lil alamin (Islam as a mercy to all creation), providing moral and spiritual education, countering radicalism through local wisdom, and serving as role models for the community.